+0

# kto12 general math

0
124
1

f(x)=4x+7 and g(x)=3x-5.find (fog)(-4)

Guest Jul 1, 2017

#1
+5573
+3

\((f\circ g)(-4)=f(\,g(-4)\,)\)

f(x)  =  4x + 7                             Replace every instance of   x   with   g(-4)   .

f( g(-4) )  =  4( g(-4) ) + 7

And.....

g(x)  =  3x - 5                             Replace every instance of   x   with   -4   .

g(-4)  =  3(-4) - 5                        Simplify.

g(-4)  =  -17

f( g(-4) )  =  4( g(-4) ) + 7             On the right side, replace   g(-4)   with   -17

f( g(-4) )  =  4( -17 ) + 7               Simplify.

f( g(-4) )  =  -61

hectictar  Jul 1, 2017
Sort:

#1
+5573
+3

\((f\circ g)(-4)=f(\,g(-4)\,)\)

f(x)  =  4x + 7                             Replace every instance of   x   with   g(-4)   .

f( g(-4) )  =  4( g(-4) ) + 7

And.....

g(x)  =  3x - 5                             Replace every instance of   x   with   -4   .

g(-4)  =  3(-4) - 5                        Simplify.

g(-4)  =  -17

f( g(-4) )  =  4( g(-4) ) + 7             On the right side, replace   g(-4)   with   -17

f( g(-4) )  =  4( -17 ) + 7               Simplify.

f( g(-4) )  =  -61

hectictar  Jul 1, 2017

### 5 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details